The contribution of nocturnal sleep to the consolidation of motor skill learning in healthy ageing and Parkinson's disease. (11th February 2013) - Terpening, Zoe; Naismith, Sharon; Melehan, Kerri; Gittins, Catherine; Bolitho, Sam; Lewis, Simon J. G.
Summary The benefits of sleep for the consolidation of procedural motor skills are less robust in older adults, although the precise reasons for this remain unclear. To date, even less is known about these processes in older adults with neurodegenerative diseases, particularly those which impact on motor functioning. While sleep disturbance and motor symptoms are frequent disabling features of Parkinson's disease, no known studies have directly probed sleep‐dependent memory consolidation for motor skill learning in Parkinson's disease. Forty patients with idiopathic Parkinson's disease (age = 63.7 years ± 7.7; disease duration 4.1 years ± 4.4) completed a motor skill learning task pre‐ and post‐sleep and were compared to 20 age‐ and sex‐matched controls recruited from the community. Polysomnography was undertaken during the post‐training night and measures of sleep architecture were derived. Parkinson's disease patients did not demonstrate any apparent deficits in within‐session learning and overnight stabilization compared to controls, with both groups failing to demonstrate offline improvements in performance (i.e. memory consolidation). In controls, longer duration in slow wave sleep was associated with improved next‐day session learning (P = 0.007). However, in Parkinson's disease, no relationships between sleep parameters and learning measures were found. Slow wave sleep microarchitecture and the use of dopaminergic medications may contribute to impaired sleep‐dependent multi‐session acquisition of motor skill learning in Parkinson's disease.